Risk of conversion to open surgery during robotic and laparoscopic pancreatoduodenectomy and effect on outcomes: international propensity score-matched comparison study. Issue 1 (31st December 2020) - Lof, S; Vissers, F L; Klompmaker, S; Berti, S; Boggi, U; Coratti, A; Dokmak, S; Fara, R; Festen, S; D'Hondt, M; Khatkov, I; Lips, D; et al.
Abstract : Risk factors for conversion during minimally invasive pancreatoduodenectomy (MIPD) include age, large tumour size, location of tumour, laparoscopic approach, and surgery in medium-volume centres. Although conversion during MIPD itself was not associated with worse outcomes, the outcome in these patients was poor in general; ;this should be taken into account during patient selection for MIPD. Abstract: Background: Minimally invasive pancreatoduodenectomy (MIPD) is increasingly being performed because of perceived patient benefits. Whether conversion of MIPD to open pancreatoduodenectomy worsens outcome, and which risk factors are associated with conversion, is unclear. Methods: This was a post hoc analysis of a European multicentre retrospective cohort study of patients undergoing MIPD (2012–2017) in ten medium-volume (10–19 MIPDs annually) and four high-volume (at least 20 MIPDs annually) centres. Propensity score matching (1 : 1) was used to compare outcomes of converted and non-converted MIPD procedures. Multivariable logistic regression analysis was performed to identify risk factors for conversion, with results presented as odds ratios (ORs) with 95 per cent confidence intervals (c.i). Results: Overall, 65 of 709 MIPDs were converted (9.2 per cent) and the overall 30-day mortality rate was 3.8 per cent. Risk factors for conversion were tumour size larger than 40 mm (OR 2.7, 95 per cent c.i.1.0 to 6.8; P = 0.041), pancreatobiliary tumours (OR 2.2, 1.0 to 4.8; P = 0.039), age at least 75 years (OR 2.0, 1.0 to 4.1; P = 0.043), and laparoscopic pancreatoduodenectomy (OR 5.2, 2.5 to 10.7; P < 0.001). Medium-volume centres had a higher risk of conversion than high-volume centres (15.2 versus 4.1 per cent, P < 0.001; OR 4.1, 2.3 to 7.4, P < 0.001). After propensity score matching (56 converted MIPDs and 56 completed MIPDs) including risk factors, rates of complications with a Clavien–Dindo grade of III or higher (32 versus 34 per cent; P = 0.841) and 30-day mortality (12 versus 6 per cent; P = 0.274) did not differ between converted and non-converted MIPDs. Conclusion: Risk factors for conversion during MIPD include age, large tumour size, tumour location, laparoscopic approach, and surgery in medium-volume centres. Although conversion during MIPD itself was not associated with worse outcomes, the outcome in these patients was poor in general which should be taken into account during patient selection for MIPD.